Differential effects of saturated and unsaturated fatty acids on vascular reactivity in isolated mesenteric and femoral arteries of rats - Vorn, Rany (Korean J Physiol Pharmacol, 2019)
Free fatty acid (FFA) intake regulates blood pressure and vascular reactivity but its direct effect on contractility of systemic arteries is not well understood. We investigated the effects of saturated fatty acid (SFA, palmitic acid), polyunsaturated fatty acid (PUFA, linoleic acid), and monounsaturated fatty acid (MUFA, oleic acid) on the contractility of isolated mesenteric (MA) and deep femoral arteries (DFA) of Sprague–Dawley rats. Isolated MA and DFA were mounted on a dual wire myograph and phenylephrine (PhE, 1–10 µM) concentration-dependent contraction was obtained with or without FFAs. Incubation with 100 µM of palmitic acid significantly increased PhE-induced contraction in both arteries. In MA, treatment with 100 µM of linoleic acid decreased 1 µM PhE-induced contraction while increasing the response to higher PhE concentrations. In DFA, linoleic acid slightly decreased PhE-induced contraction while 200 µM oleic acid significantly decreased it. In MA, oleic acid reduced contraction at low PhE concentration (1 and 2 µM) while increasing it at 10 µM PhE. Perplexingly, depolarization by 40 mM KCl-induced contraction of MA was commonly enhanced by the three fatty acids. The 40 mM KCl-contraction of DFA was also augmented by linoleic and oleic acids while not affected by palmitic acid. SFA persistently increased alpha-adrenergic contraction of systemic arteries whereas PUFA and MUFA attenuated PhE-induced contraction of skeletal arteries. PUFA and MUFA concentration-dependent dual effects on MA suggest differential mechanisms depending on the types of arteries. Further studies are needed to elucidate underlying mechanisms of the various effects of FFA on systemic arteries.